A self-restorable architecture for bidirectional wavelength-division-multiplexed passive optical network with colorless ONUs - Lee, Kwanil; Lee, Sang Bae; Lee, Ju Han; Han, Young-Geun; Mun, Sil-Gu; Lee, Sang-Mook; Lee, Chang-Hee (OPTICAL SOC AMER, 2007)
We propose and experimentally demonstrate a novel protection scheme for wavelength-division-multiplexed passive optical network (WDM-PON) employing colorless optical transceivers. The proposed network employs 2 x N arrayed waveguide gratings (AWGs) to utilize its routing characteristics. The colorless operation is achieved by using wavelength-locked Fabry-Perot laser diodes (FP-LDs) injected with spectrum-sliced amplified spontaneous emission (ASE) light. The experimental results show that the restoration can be achieved within 8 ms against the feeder fiber fault and the power penalty introduced by the restoration process is negligible. (c) 2007 Optical Society of America.
Keywords: SCHEME